Effect of an inhaled glucocorticoid on reactive oxygen species production by bronchoalveolar lavage cells from smoking COPD patients - Gert T. Verhoeven; Annemarie J.M. Wijkhuijs; Herbert Hooijkaas; Henk C. Hoogsteden; Wim Sluiter (Mediators of Inflammation)
Oxidative stress in the lung is important in the pathogenesis of COPD. Published data indicate that glucocorticoids inhibit blood cells in their capacity to produce reactive oxygen species (ROS). We investigated the effect of Fluticasone propionate (FP) on the ROS production capabilities of pulmonary cells. Bronchoalveolar lavage (BAL) was performed in smoking COPD patients, before and after a six month, placebo-controlled treatment with FP. BAL cells were stimulated with phorbol myristrate acetate (PMA) alone, and together with superoxide dismutase (SOD). From kinetic plots of ferricytochrome-c conversion we calculated the maximal rate of superoxide production: Vmax. We also examined BAL cell subsets and performed correlation analyses on ROS production and relevant clinical determinants. Paired results were obtained from 6 FP- and 9 placebo-treated patients. No significant change of Vmax was found in both patient groups. Also BAL cellularity was unchanged. Correlation analyses showed a significant (inverse) association of Vmax with the number of cigarettes smoked per day. We concluded that a potent inhaled glucocorticoid had no effect on the ROS production capability of BAL cells from smoking COPD patients. Apparently, heavy smoking impaired the ability of alveolar macrophages to produce ROS, which was not further decreased by FP.